Water-security in Ethiopia and the Emotional response of Pastoralists (WEEP) data - Hutchings, Paul; Cooper, Sarah (Cranfield University, 2020)
Anonymised dataset from survey study of pastoralists in Afar, Ethiopia (June 2018). Survey collected data on sociodemographics, water, sanitation and hygiene access as well as emotional response to water security issues. It was part of an ESRC project titled: Water-security in Ethiopia and the Emotional response of Pastoralists (WEEP). (ES/R001049/1). 2017-2019.
Keywords: Water security'; 'sanitation access'; 'pastoralists'; 'Wellbeing Analysis'; 'Environmental Sociology'